2011
DOI: 10.1515/1542-6580.2479
|View full text |Cite
|
Sign up to set email alerts
|

Production of L-asparaginase from Natural Substrates by Aspergillus terreus MTCC 1782: Optimization of Carbon Source and Operating Conditions

Abstract: In the present work, the effect of different carbon sources, namely glucose, sucrose, maltose, fructose and lactose, was studied for extracellular L-asparaginase production by Aspergillus terreus MTCC 1782 in submerged fermentation. The best carbon source and operating conditions such as initial pH, inoculum size, temperature and agitation rate were optimized. Glucose was found to be the best carbon source for L-asparaginase production using modified Czapek-Dox media containing L-proline as substrate. Sucrose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
3
4
0
Order By: Relevance
“…Stimulation of the production occurred at low glucose concentrations while inhibition happened at high concentrations which may be due to the catabolic repression effect of glucose. The same results were reported by other workers (El-Hefnawy et al 2015;Gurunathan and Sahadevan 2011). Enzymes productions are highly dependent on the used sources of nitrogen, since these sources affect nucleic acid production and cell wall and protein biosynthesis.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Stimulation of the production occurred at low glucose concentrations while inhibition happened at high concentrations which may be due to the catabolic repression effect of glucose. The same results were reported by other workers (El-Hefnawy et al 2015;Gurunathan and Sahadevan 2011). Enzymes productions are highly dependent on the used sources of nitrogen, since these sources affect nucleic acid production and cell wall and protein biosynthesis.…”
Section: Discussionsupporting
confidence: 86%
“…In the present study dextrose proved to have a positive effect on l-asparaginase biosynthesis by the test organism as it increased the production level of this enzyme. Other authors also reported that dextrose increases the production of l-asparaginase as in case of Aeromonas sp., Aspergillus terreus (Amena et al 2010;Doriya and Kumar 2016;El-Hefnawy et al 2015;Gurunathan and Sahadevan 2011;Varalakshmi and Raju 2013). However, other carbohydrate sources were reported for their enhancing effect on l-asparaginase biosynthesis as in case of sucrose and sorbitol for Streptomyces tendae (Kavitha and Vijayalakshmi 2010) and lactose in case of E. coli (Bahrani 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The highest L-asparaginase levels (5.558 U/ml), (4.95 U/ml) and (4.923 U/ml) were produced by C. tenuissimum, A. carneus and P. camemberti, respectively in MCD medium containing 0.2% glucose ( Figure 2). These findings are consistent with research done by Gurunathan and Sahadevan [12], Raja et al [13] and Zia et al [14].…”
Section: Effect Of Carbon Sourcesupporting
confidence: 93%
“…Increase in the production of L-asparaginase with 0.1% glucose could be due to the fact that it is a simple and easily soluble sugar therefore, readily metabolized by fungi. It was also reported that glucose supported L-asparaginase production in other fungi such as Aspergillus terreus MTCC1782, Fusarium oxysporum and Trichoderma viride F2 (Gurunathan and Sahadevan, 2011;Pallem et al, 2011;Elshafei and El-Ghonemy, 2015). But on the other hand, glucose was also reported to be a repressor of Lasparaginase in Enterobacter aerogenes (Mukherjee et al, 2000).…”
Section: Effect Of Supplementation Of Carbon and Nitrogen Sourcesmentioning
confidence: 97%